Risk factors associated with retained placenta in dairy cattle in northern Mexico - Carrera Chavez, Jose Maria (2019)
The objective was to determine the association between different risk factors for placental retention (PR) in northern Mexico. Records of 2 492 Holstein cows from a commercial dairy herd located in Ciudad Juárez, Chihuahua, Mexico were used. Variables were analyzed by the chi-square test (c2) test and odds ratios (OR) were calculated to determine the association of the risk factors with PR. The total incidence of PR was 10.15%. The risk factors associated with RP were twin birth and premature birth, followed by stillbirths and dystocia. The presence of RP did not increase the number of inseminations, but decreased the days in milk in affected cows (p < 0.05). In conclusion, the risk factors twin birth, premature birth, stillbirth, dystocia and age of the cow affect the incidence of RP, while the delivery season does not predispose to the presentation of this alteration.